Demokrasi Indonesia: Dinamika, tantangan dan penguatan demokrasi di era modern - ROMADHONI_, JAYA KUSUMA (Maliki Interdisciplinary Journal, 2026)
Democracy is a system of government that provides opportunities for citizens to participate in determining state policies. Indonesia implements Pancasila democracy which is based on the values of deliberation, mutual cooperation, and respect for diversity. This study aims to analyze the development of democracy in Indonesia, the challenges it faces, and the efforts to strengthen democracy in the era of reform and digitalization. The research method used is qualitative research with a library research approach through the review of scientific journals, books, academic articles, and other scholarly sources. The results show that the development of democracy in Indonesia has evolved from the parliamentary democracy period, guided democracy, the New Order era, to the reform era which provides greater freedom for political participation and civil liberties. However, Indonesian democracy still faces various challenges such as money politics, political corruption, identity politics, social polarization, and low levels of political education among society. Therefore, strengthening political education, law enforcement, the independence of democratic institutions, digital literacy, and the values of Pancasila is essential to create a healthy, fair, and integrity-based democracy.